Inventory of Understorey with Potential as Botanical Insecticide in Cultivated Area the Kamojang Crater, Cikaro River Sub-Watershed - Rasiska, Siska; Sudarjat, Sudarjat; Parikesit, Parikesit; Asdak, Chay; Gunawan, Budhi (CROPSAVER, 2026)
Botanical insecticides are one of the alternatives to control vegetable plant insect pests that are considered effective and efficient. However, in its implementation there are obstacles, including information about understorey that have the potential to be botanical insecticides. This study aims to inventory understorey as botanical insecticides in the cultivation area Kamojang Crater of the Cikaro subwatershed. The method used in this study is exploration by sampling transects with a radius of 500 meters. Each path is determined by 5 observation points, so that 20 observation plots are obtained in the cultivation area near nature reserves (NA), nature tourism parks (NTP), protected forests (PF), and agricultural land (AL). The understorey were found then identified, calculated their density, frequency, dominance, important value index, species diversity, type richness, evenness, and dominance. The results showed that 41 families, 93 species, and 3,355 individuals of understorey were found. A number of families and species of plants have the potential to be botanical insecticides such as Asteraceae, Fabaceae, Euphorbiaceae, Malvaceae, Lamiaceae, and Rutaceae, with the species being Ageratina riparia; Imperata cylindrica; Chromolaena odorata; Etlingera elatior; Centela asiatica;  Lantana camara; Mimosa pudica; Pennisetum purpureum;  Ageratum conyzoides;  Cynodon dactylon;  Galinsoga parviflora;  and Althenantera philoxeroides. The diversity of understorey species with the potential as botanical insecticides is categorized  medium (2.404<H'<2.752), with a high species richness index (5.352<E<6.196), and a high evenness index (0.666<R<0.736), as well as a low dominance index (0.117<C<0.183). and the biopesticides species in cultivated areas near NTP have strong type similarities with AL.